LDL in patients with subclinical hypothyroidism shows increased lipid peroxidation - Zha, Kexi (Lipids Health Dis, 2015)
BACKGROUND: Population-based studies have demonstrated that subclinical hypothyroidism (SCH) is an independent risk factor for atherosclerosis (OR = 1.9). However, this connection cannot be entirely explained by dyslipidemia accompanied by SCH. Lipid peroxidation also plays an important role in the development of atherosclerosis. In this study, we aimed to evaluate oxidative stress in SCH patients, as measured according to concentrations of hydroxy-octadecadienoic acids (HODEs) and hydroxy-eicosatetraenoic acids (HETEs) in both plasma and low density lipoproteins (LDL). SUBJECTS AND METHODS: The concentrations of HODEs and HETEs in both LDL and plasma were examined in euthyroid (n = 10), mild SCH (4.5 ≤ TSH <10 mU/L, n = 10), and significant SCH (TSH ≥ 10 mU/L, n = 10) subjects, using a liquid chromatograph-electrospray ionization- mass spectrometer. Then, we explored the relationship among LDL oxidation, TSH levels, and carotid intima-media thickness (IMT), a biomarker of subclinical atherosclerosis. RESULTS: Serum LDL-C levels and mean-IMT in the significant SCH group were higher than in the euthyroid group (p < 0.05). The HODE and HETE concentrations clearly increased in the significant SCH patients compared with the euthyroid subjects, but there was no difference between the mild SCH and euthyroid groups. Among all subjects, linear and significant positive correlations were identified between TSH and mean-IMT after adjustment for confounding factors (r = 0.480, p = 0.018). Both 9-HODE (r = 0.376, p = 0.041) and 13-HODE (r = 0.447, p = 0.013) in LDL were linearly and positively correlated with TSH. The concentrations of HODEs (both 9-HODE and 13-HODE) in LDL were much higher in the thickened IMT group than in the normal IMT group (p = 0.017 and 0.015, respectively). HODEs in LDL were also positively associated with mean-IMT. CONCLUSIONS: Our findings showed that lipid peroxidation was higher in the significant SCH patients than in the euthyroid subjects, which suggested that qualitative as well as quantitative changes in serum lipids resulting from SCH may add to atherosclerosis risk. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12944-015-0092-4) contains supplementary material, which is available to authorized users.